RISE: NANO-ElecTronic (NET) research group / Assoc. Prof. Ir Ts. Dr Mohamad Hafiz Mamat - Mamat, Mohamad Hafiz (Office of the Deputy Vice-Chancellor (Research & Innovation), 2021)
The NANO-ElecTronic (NET) Research Group is one of the active research groups in the School of Electrical Engineering, College of Engineering, UiTM conducts nanotechnology-related research with high-end nanofabrication facilities.